2009
DOI: 10.1007/s11244-009-9207-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Carbon Nanotube-Supported Pt Metal Particles Covered with Silica Layers and Their Application to Electrocatalysts for PEMFC

Abstract: Carbon nanotube (CNT)-supported Pt metal nanoparticles were covered with silica layers by hydrolysis of 3-aminopropyl-triethoxysilane (APTES) and/or tetraethoxysilane (TEOS). The hydrolysis of only APTES resulted in a uniform coverage of silica layers on Pt/CNT, but the thickness of the silica layers was very thin (\1 nm). Pt/CNT could also be coated with silica layers of a few nanometers in thickness by hydrolysis of TEOS, but exposed surfaces of CNTs in the sample were frequently observed. In contrast, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Core-shell catalysts that consist of active metal particles surrounded by porous oxides have drawn much attention because of their enhanced catalytic activity and stability in water-gas shift reactions [1][2][3], dry reforming of methane [4][5][6][7][8][9], hydrocarbon oxidation [10], electrocatalysis [11][12][13][14][15][16], photocatalytic water splitting [17,18], and hydrogenation reactions [19][20][21]. A water-in-oil reverse microemulsion system consists of thermodynamically stable nanosized aqueous micelles surrounded by self-assembled surfactant dispersed in an organic solvent [22].…”
Section: Introductionmentioning
confidence: 99%
“…Core-shell catalysts that consist of active metal particles surrounded by porous oxides have drawn much attention because of their enhanced catalytic activity and stability in water-gas shift reactions [1][2][3], dry reforming of methane [4][5][6][7][8][9], hydrocarbon oxidation [10], electrocatalysis [11][12][13][14][15][16], photocatalytic water splitting [17,18], and hydrogenation reactions [19][20][21]. A water-in-oil reverse microemulsion system consists of thermodynamically stable nanosized aqueous micelles surrounded by self-assembled surfactant dispersed in an organic solvent [22].…”
Section: Introductionmentioning
confidence: 99%
“…Pt/CNTs were covered with silica layers by hydrolysis of 3‐aminopropyltriethoxysilane and/or tetraethoxysilane (TEOS). The silica‐coated Pt/CNT showed high catalytic activity for electrochemical reactions in aqueous H 2 SO 4 electrolyte, despite the uniform coverage of the Pt metal with silica layers 10. Pt/CNT11 and PtAu/CNT12 catalysts were covered by a porous SiO 2 layer to improve their thermal and electrochemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Takenaka et al used silica coated carbon nanotube (CNT) as support material and reported that silica-coating improved the durability of Pt/CNT electrocatalysts (22). Although it has negatively affected the conductivity and hydrophobicity of the catalyst layer, Travitsky et al used SiO 2 as a support material (23).…”
Section: Introductionmentioning
confidence: 99%